Swimming Performance and Oxygen Consumption Rate of Juvenile Asian Seabass (Lates calcarifer) at Different Water Velocities - Khongthon, Suthathip; Jongjaroensuk , Roongparit; Taparhudee, Wara (Burapha Science Journal, 2026)
This study aims to determine an optimal water velocity on swimming performance of juvenile Asian seabass (16.07 ± 0.67 cm total length and 56.4 ± 3.11 g body weight) and oxygen consumption rate at different water velocities (0, 8, 16, 24 and 32 cm/s). The experiment was done in respirometer modified from Brett’s style (1964). The swimming performance test was measured by critical swimming speed (Ucrit1 and Ucrit2) method and endurance performance method. The Ucrit1 test, each fish was transferred into the respirometer without flow (0 cm/s) of 30 minutes, and then subjected to a flow of 8 cm/s for 20 minutes. Then the water velocity was increased by 8 cm/s every 10 minutes until the fish was not able to swim and it was pushed back to the end of the pipe. The Ucrit2 test was carried out on the fish in the respirometer with the water velocity of 10 cm/s in 60 minutes and then, increase the water velocity of 16 cm/s and increased at 8 cm/s every 10 minutes as Ucrit1 method mentioned earlier. After that the endurance performance test was performed using the water velocity starting from average of Ucrit1 and Ucrit2 results for 60 minutes. The results of swimming performance (Ucrit1, Ucrit2 and endurance) in the juvenile Asian seabass were 56.43 cm/s, 57.23 cm/s and 33.2 cm/s, respectively. An average oxygen consumption rate of juvenile Asian seabass at 0 cm/s was 8.1±3.4 mgO2/kg/hr that differed significantly (P<0.05) compared with of water velocity at 8, 16, 24 and 32 cm/s, which the oxygen consumption rates were 62.6±1.6, 65.7±4.3, 68.3±13.2 and 72.9±1.3 mgO2/kg/hr, respectively.